2021
DOI: 10.1007/s11154-021-09667-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses of light and taste receptors – unexpected actions of GPCRs in adipocytes

Abstract: The G-protein-coupled receptor (GPCR) superfamily includes sensory receptors that can detect and respond to taste and light. Recent investigations have identified key metabolic roles for such receptors in tissues considered ‘non-sensory’ such as adipose tissue. The major functions of white and brown adipose tissues include energy storage/release and thermogenesis, respectively. These processes are tightly controlled by GPCR pathways that serve to maintain energy homeostasis. Opsins 3 and 4 are GPCRs activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Animal models demonstrated that a high-fat diet down-modulates OPN3 in white adipocytes, and the latter protects from diet-induced obesity and insulin resistance. Exposing brown adipose tissue to led light leads to an increase in glucose uptake and glucose-dependent mitochondrial respiration in the wild type, whilst cells knocked out for OPN3 did not show any consequence after exposure [ 46 ]. Modern sleep rhythms and over- or under- exposure to blue light are likely to alter opsin stimulation and in turn to contribute to the insurgency of type 2 diabetes.…”
Section: Type 2 Diabetes and Circadian Rhythmmentioning
confidence: 99%
“…Animal models demonstrated that a high-fat diet down-modulates OPN3 in white adipocytes, and the latter protects from diet-induced obesity and insulin resistance. Exposing brown adipose tissue to led light leads to an increase in glucose uptake and glucose-dependent mitochondrial respiration in the wild type, whilst cells knocked out for OPN3 did not show any consequence after exposure [ 46 ]. Modern sleep rhythms and over- or under- exposure to blue light are likely to alter opsin stimulation and in turn to contribute to the insurgency of type 2 diabetes.…”
Section: Type 2 Diabetes and Circadian Rhythmmentioning
confidence: 99%
“…G protein-coupled receptors (GPCRs), which are known as the most diverse superfamily of membrane receptors, are composed of N-terminal and C-terminal regions alongside a highly conserved seven-transmembrane (7TM) core backbone . Functioning as the primary signaling receptors, GPCRs play critical regulatory functions across a range of physiological processes, including cellular metabolism, hormone secretion, behavioral and emotional regulation, and the immune system. By manipulating the regulatory actions of GPCRs, it is possible to modulate the normal receptor function, ultimately resulting in the death or decreased reproductive capacity of pests, thereby reducing their populations . It was widely believed that olfactory receptors (ORs) in C. pomonella were G protein-coupled receptors capable of binding to a diverse array of odor molecules, thereby influencing the olfactory perception.…”
Section: Introductionmentioning
confidence: 99%
“…Although OPN3 is highly expressed in different brain areas, its precise function in these regions remains unidentified, aside from modulating the Acoustic Startle Reflex (ASR), which is an involuntary, rapid contraction of skeletal muscle in response to a sudden, intense auditory stimulus [29]. Notably, in adipocytes, OPN3 has been linked to the conversion of white adipose tissue to thermogenic brown adipose tissue [30], suggesting a thermosensitive nature for OPN3. This could explain its presence in body areas not typically exposed to light rays, such as adipose tissue and even the heart, as described in an interesting article by Prof. de Lauro Castrucci's group [7].…”
mentioning
confidence: 99%